Impairment of the organization of locomotor and exploratory behaviors in bile duct-ligated rats. - Renata Leke (Public Library of Science (PLoS), 2012)
Hepatic encephalopathy (HE) arises from acute or chronic liver diseases and leads to several problems, including motor impairment. Animal models of chronic liver disease have extensively investigated the mechanisms of this disease. Impairment of locomotor activity has been described in different rat models. However, these studies are controversial and the majority has primarily analyzed activity parameters. Therefore, the aim of the present study was to evaluate locomotor and exploratory behavior in bile duct-ligated (BDL) rats to explore the spatial and temporal structure of behavior. Adult female Wistar rats underwent common bile duct ligation (BDL rats) or the manipulation of common bile duct without ligation (control rats). Six weeks after surgery, control and BDL rats underwent open-field, plus-maze and foot-fault behavioral tasks. The BDL rats developed chronic liver failure and exhibited a decrease in total distance traveled, increased total immobility time, smaller number of rearings, longer periods in the home base area and decreased percentage of time in the center zone of the arena, when compared to the control rats. Moreover, the performance of the BDL rats was not different from the control rats for the elevated plus-maze and foot-fault tasks. Therefore, the BDL rats demonstrated disturbed spontaneous locomotor and exploratory activities as a consequence of altered spatio-temporal organization of behavior.